Toward highly efficient in situ dry reforming of H2S contaminated methane in solid oxide fuel cells via incorporating a coke/sulfur resistant bimetallic catalyst layer. Issue 23 (24th May 2016) - Hua, Bin; Yan, Ning; Li, Meng; Sun, Yi-Fei; Chen, Jian; Zhang, Ya-Qian; Li, Jian; Etsell, Thomas; Sarkar, Partha; Luo, Jing-Li
Abstract : We demonstrated an electrochemical dry reforming of sour methane process to co-produce CO2 -derived syngas and energy in an efficient and coke/sulfur resistant way. Abstract : The escalating global warming effects are a reason for immediate measures to reduce the level of greenhouse gases. In this context, dry reforming of methane (DRM), an old yet both scientifically and industrially important process, is making a comeback in contributing to the utilization of CO2 . However, catalyst deactivation (sulfur poisoning and coke formation) and the associated high energy consumption remain technological hurdles to its practical implementation. Here we demonstrated that dry reforming of H2 S-containing CH4 can be efficiently conducted in conventional solid oxide fuel cells via incorporating a coke/sulfur resistant catalyst layer. The add-on layer, composed of tailored Ce0.8 Zr0.2 O2 supported NiCu nanoclusters, demonstrated outstanding in situ reforming activity while possessing reasonable coke/sulfur resistance. At 800 °C and in a 50 ppm H2 S containing CH4 –CO2 mixture, the cell had a maximum power density of 1.05 W cm −2, a value high enough for practical application. Through H2 selective oxidation, the energy required for DRM was partially compensated for and the produced water greatly suppressed the carbon deposition. This study offers a new dimension in cogenerating CO2 -derived synthesis gas and electrical power in the context of increasing interests in efficient utilization of H2 S-containing CH4 and CO2 .